Use of Garden Design to Enhance Mental Health Among the Selected Health Facilities in Kabale Town: A Case Study of Makanga Health Facility. - Nayebare, Maria (Kabale University, 2024)
The research aims at exploring and creating new garden designs for therapeutic purposes that are sustainable environments associated with mental health. Garden design encompasses the art and science of planning, arranging, and creating outdoor spaces that are both functional and aesthetically pleasing. Whether you have a sprawling backyard or a cozy balcony, garden design involves thoughtful consideration of various elements. Therapeutic gardens are intentionally designed outdoor spaces that aim to enhance mental and physical health through interactions with nature. According to (de la Motte, 2014, August), “Therapeutic gardens are becoming increasingly popular, particularly in special needs settings such as disability centers, aged care, hospitals, and rehabilitation centers”. Although therapeutic garden designs follow the same principles as general garden design, this research seeks to illustrate those factors that are unique to a number of special needs groups. Four different designs have been analyzed for actual projects that have been recently completed. Included are gardens in a geriatric ward of a major metropolitan hospital, a rehabilitation center garden in suburban Melbourne, an aged care facility in country Victoria, and a disability day care center garden. The research emphasizes the importance of reconnecting humans with their environment and highlights the therapeutic potential of nature. Historically, plants played a significant role in hospital architecture, especially in sanatoriums treating tuberculosis and mental illnesses. However, over time, natural spaces disappeared from medical buildings due to hygiene-focused approaches. Recent scientific research challenges this trend, suggesting that gardens and nature can be more potent than medicine itself. Thus the Healing Gardens initiative aims to reintegrate nature into health care systems through public policy. The healing garden design focuses on maximizing patients' well-being by incorporating physical, psychological, emotional, and social elements. by bringing the benefits of garden spaces into hospitals, these gardens contributed to the patient’s recovery processes. Healing gardens should provide a sense of security and safety, incorporating elements like trees, flowers, fragrant plants, and shrubs to evoke a feeling of hope and relaxation. Therefore, one has to consider the balance between physical activities and passive experiences in the garden to maximize its benefits. The design firstly should be functional and aesthetically appealing thus offering enough space for different activities. The success of healing gardens is in the ability to give mental restoration and therapeutic benefits through passive and active engagement. by using different elements like water features, natural materials, seating areas,s and focal points for meditation thus the aim is to reduce stress, improve mood, and enhance overall well-being.